The Defects of Infectious Diseases Residency Curriculum in Iran - Abbas Alami; Fariba Derakhshan (Kerman University of Medical Sciences, 2014)
Background & Objective: To train specialists in infectious diseases a comprehensive and responsive curriculum to community needs is essential We checked the infectious diseases residency curriculum in Iran and comprised it with same curricula of other country with the aim of identifying the defects   Methods: This descriptivecomparative study had three steps First researchers studied the infectious diseases curriculum of Iran Then the same curricula in some other countries were extracted and finally information such as mission and goals type and duration of postgraduate training and rotations teaching strategies and approaches and amount of elective courses were compared within these curricula   Results: In Iran the curricula of postgraduate courses for all medical universities are formulated by Ministry of Health There are many similarities between infectious diseases residency curriculum of Iranian universities and other countries but in many countries it is offered in fellowship courses In Iranian domestic curriculum learning objectives themes and subthemes assessment methods blueprint and rotational period details are not mentioned However other issues such as the epidemiology and health issues are considered in the shortterm courses Based on domestic curriculum resident cannot be selectively trained in any course or procedure Most of the instructional content of curriculum was organized by topics   Conclusion: Policy makers in Iranian Ministry of Health should attend internal consistency of infectious diseases residency curriculum considering other trainee levels curricula and utilize exclusive subjectbased models in curriculum formulation to promote education in this field